Variasi Musiman Komunitas Reptil Di Hutan Kemuning, Jawa Tengah: Seasonal Variation Of Reptile Communities In Kemuning Forest, Central Java - Letus Sepsamli; Imam Hidayat (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Reptiles play an important ecological role in maintaining the balance of tropical forest ecosystems. This study aimed to describe the reptile community during the dry and rainy seasons in the Kemuning Forest, Central Java, and to identify the influence of temperature and humidity variations on reptile diversity and activity patterns. Observations were conducted using the Visual Encounter Survey (VES) method combined with line transects during two sampling periods: May–June (dry season) and November 2016 (rainy season). Species diversity was calculated using the Shannon-Wiener Index (H′). The results recorded 12 species. The diversity index of reptiles was moderate, indicated by H′ = 1.65 in the dry season and H′ = 1.41 in the rainy season. Warmer microclimatic conditions during the dry season supported thermoregulatory activities of diurnal species such as Eutropis multifasciata and Draco haematopogon, while lower temperatures and higher humidity during the rainy season reduced surface activity. These findings indicate that temperature and humidity are the main factors regulating the structure and dynamics of tropical reptile communities and emphasize the importance of thermal ecology-based habitat management to support reptile conservation in the Kemuning Forest.